Use of Industrial Wastes as Filler in Open-Graded Friction Courses - Rajan Choudhary; Dibyatonu Chattopadhyay; Abhinay Kumar; Ashok Julaganti (The Baltic Journal of Road and Bridge Engineering)
For a fast developing economy like India, expansion, rehabilitation, and maintenance of transportation infrastructure is crucial and require huge quantities of high quality natural aggregates. Meanwhile, vast amounts of industrial wastes accumulating in the country pose problems related to safe and sustainable disposal. The present study investigated possible utilisation of marble dust, a waste from stone industry, and fly ash, a waste from thermal power stations, as filler materials in open-graded friction course mixes. Open-graded friction course mixes incorporating fly ash, marble dust, and two sources of stone dust as filler fractions were designed and evaluated for mix design properties including draindown, abrasion loss, air void content, and permeability. Morphology of each filler was characterised through scanning electron microscopy. Physicochemical properties of fillers were examined through Rigden voids, German filler test, methylene blue, and hydrometer analysis. Analysis of variance using Fisher multiple comparison procedure was performed to evaluate the effect of filler type on design properties of open-graded friction course mixes. Regression analysis using forward selection technique was performed to identify significant filler characteristics influencing open-graded friction course properties. Results showed that filler type affected open-graded friction course design parameters significantly. Open-graded friction course mixes with marble dust showed promising performance with lowest draindown, and highest durability, air voids, and permeability. Regression analysis identified Rigden void content of filler materials as a major filler characteristic affecting the mix design parameters of open-graded friction course mixes.